Teaching for transfer: exposure, experiences & instructional behavior of instructors in higher education - Rausch, Thomas Alan, author; Kaiser, Leann, advisor; Enns, Kellie, committee member; Folkestad, James, committee member; Zarestky, Jill, committee member (Colorado State University. Libraries, 2023)
Learning transfer, the ability to apply learning from one situation to another, is expected of students and underlies the entire structure in higher education. Yet, many instructors in higher education do not know what learning transfer is or how to accomplish it. In an effort to understand how instructors in higher education came to teach for transfer, this study investigated the exposure, experiences, and instructional behavior of university and college instructors who self-identified as those who "teach for transfer." The purpose of this study was to understand the context and circumstances of instructor's experiences surrounding teaching for transfer, and how those experiences ultimately affected their instructional behavior. Using a basic qualitative study, the researcher recruited instructors in higher education who self-identified as those who teach for transfer in a university or college setting to take part in semi-structured interviews. Six major themes emerged from the analysis including leaning transfer experiences as students, role modeling as a teaching assistant, formalized content experiences, improving teaching for transfer, barriers to teaching for transfer, and unfamiliar with learning transfer terminology. The findings highlight how experiences affected instructional behavior of those teach for transfer. The study can help academics understand the link between experiences and instructional behaviors and address the barriers present which affect teaching for transfer.
Keywords: instructional design; teaching for transfer; learning transfer; instructional behavior